2019
DOI: 10.1093/jpepsy/jsz087
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Interventions Targeting Recovery in Child and Adolescent Burns: A Systematic Review

Abstract: Children post-burn injury experience a range of psychosocial sequelae that benefit from early provision of psychosocial support. However, no systematic review exists evaluating the full range of psychological interventions. Objective To critically evaluate psychosocial interventions for children (<18 years old) with burn injuries in improving psychosocial recovery. Study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…This systematic review highlights a gap in understanding the effectiveness of psychosocial interventions for Aboriginal and Torres Strait Islander paediatric burn patients' and their caregivers. Previous systematic reviews have not accounted for this specific group [60][61][62][63][64], assessed the effects of all psychosocial interventions available [60,61], or considered psychological trauma as a primary outcome [60][61][62][63]. To the authors' knowledge, this systematic review is the first to assess the effectiveness of psychosocial interventions in reducing pain and/or anxiety, distress, and trauma symptoms among paediatric burn patients and their caregivers as well as their relevance to Aboriginal and Torres Strait Islander peoples.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review highlights a gap in understanding the effectiveness of psychosocial interventions for Aboriginal and Torres Strait Islander paediatric burn patients' and their caregivers. Previous systematic reviews have not accounted for this specific group [60][61][62][63][64], assessed the effects of all psychosocial interventions available [60,61], or considered psychological trauma as a primary outcome [60][61][62][63]. To the authors' knowledge, this systematic review is the first to assess the effectiveness of psychosocial interventions in reducing pain and/or anxiety, distress, and trauma symptoms among paediatric burn patients and their caregivers as well as their relevance to Aboriginal and Torres Strait Islander peoples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have not accounted for this specific group [59][60][61][62][63], assessed the effects of all psychosocial interventions available [59,61], or considered psychological trauma as a primary outcome [59][60][61][62]. To the authors' knowledge, this systematic review is the first to assess the Similarly, only two studies provided interventions to caregivers and focused on their symptoms [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, evidence regarding distraction techniques is lacking for burn-related itch [5]. Plus, the high cost of virtual reality or multimodal devices, the need for training and technical support, and the lack of tailoring and consensus on the optimal method of delivery and technology may limit the use of distraction techniques [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although research has indicated the benefits of hypnotherapy for children with a range of conditions, data is limited in paediatric burns. Only one recently conducted randomised controlled trial (RCT) on hypnotherapy for pain and anxiety in children with burns has been identified in a recent systematic review [6]. The RCT involving some of the current authors indicated that parents of children with acute burns expressed more satisfaction with hypnotherapy in comparison to standard care at the 3rd dressing change [18].…”
Section: Introductionmentioning
confidence: 99%